Pobreza material, juventude, disciplina e sonhos: a utopia urbana em questão. Estudo sobre a Cidade dos meninos em Ribeirão das Neves/MG - Oliveira, Paulo Henrique Lima de (2007)
The purpose of this study is to analyse how the process of metropolization of Belo Horizonte, the capital of the state of Minas Gerais, Brazil, fell upon the cotidianity and ways of life of the population of Ribeirão das Neves, a municipality of the Metropolitan Region of Belo Horizonte (MRBH). It tries to give special prominence to those who, in a certain way, opted to live outside the turbulent movement of the city in question and discusses a philanthropic project entitled Town of the Boys Saint Vincent of Paola ( Cidade dos Meninos São Vicente de Paula ), which we will refer to, in this study, as Town of the Boys (TOTB/CDM), as it is known by the local community. The relation metropolis/urban periphery is described in this research from the observation of the uses and of the impossibilities pointed out by the philanthropic ideals, which are sustained by the discourse of preservation of the christian moral and of the maintenance of order. People are seduced by the idea of living far away from the urban problems and conflicts. They seek alternatives for this dilemma, putting the biggest distance possible between themselves and the areas commonly considered dangerous or risky. They choose to withdraw from more intense personal relations and sometimes shut themselves in ghettoes or groups as such. The Town of the Boys points to ways that try to give answers to the urban conflicts in the municipality where it was constructed. One of the solutions for not living the negative aspects found in Ribeirão das Neves is to invite hundreds of young people to experiment the boarding school regime. In this way, apparently, the materially deprived youth would stay far away from the drugs (and from the family), from sex (and from parties), from vandalism (and from public spaces), from violence (and from individual autonomy), from economical precariousness (and from the natural dynamics of the municipality). These are choices which give indications that the urban phenomenon fragments itself and that the cities utopia loses importance. There is no place for everybody in the urban dynamics. The full living of the city gives place to the seduction of the walls that protect and mask part of the reality. This research tries to perceive and explain that in this relation of the metropolis of Minas Gerais with its metropolitan region, a philanthropic institution gains prominence for its proposals, which are presented to hundreds of young people, about how to succeed in life through the preparation for the work market. The young and not qualified labor force which makes constant use of the metropolis feels proud and esteemed with such incentive. Lives are transformed, dreams are stimulated, a new world announces itself. The institution Town of the Boys , paradoxically, legitimates the power of the private initiatives of assistance and shows that the discourse of discipline, moral and obedience seduces and brings with itself the idea of the absence of the State as an instrument that regulates order. The preparation for the work appears as a form of domination and of capture of the dreams of those who live in the periphery in the capital of Minas Gerais. Such dreams many times become real, possible.